Understanding Consumer Behavior In Murabahah Financing Choices: The Role Of Knowledge - Ariyanti, Rini; Aziz, Roikhan Mochamad; Nurrokhim, Isma; Maghfiroh , Fachrial Lailatul; Subandono, Agus (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2025)
This study aims to understand consumer behavior in choosing murabahah financing at BMT Beringharjo Nganjuk Branch, focusing on the role of consumer knowledge as the main factor influencing decision-making. This study uses a quantitative method with a simple linear regression analysis technique. Data were collected through questionnaires for 66 respondents who are BMT customers. The results of the study indicate that consumer knowledge has a significant influence on murabahah financing decision-making, with a correlation coefficient of 0.796 (strong relationship) and an R² value of 63.4%. This indicates that 63.4% of the variability in consumer decisions can be explained by their level of knowledge, while 36.6% is influenced by other factors. Education through family and friends is the main source of information (60.6%), while electronic media and brochures are less effective. In conclusion, increasing consumer knowledge, especially through product education, can encourage more informed decisions and strengthen trust in sharia financing. This study is relevant in formulating marketing and education strategies to improve consumer understanding and BMT competitiveness in the sharia financial sector.